2015
DOI: 10.1111/aab.12190
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting virus disease in seed potatoes using flight activity data of aphid vectors

Abstract: We compiled data from the Swiss seed certification programme for the country-wide incidence of viruses in seed potato crops for the years 1989-2012. Model selection techniques were used to regress year-to-year variation in the incidence of potato viruses -largely dominated by Potato virus Y (PVY) -in three susceptible varieties against the abundance of virus vectors (winged aphids), obtained in a suction trap, to identify the most important vector species. The ultimate aim of this study was to develop a decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…For example, Congdon et al [22] developed an empirical model to forecast pea seed-borne mosaic virus (PSbMV) incidence in field pea crops using pre-growing season rainfall to calculate an index of aphid abundance which is used in combination with the virus infection level in the sown seed, to provide forecasts before sowing to allow sufficient time to implement control recommendations. Similarly, Steinger et al [23] observed that the post-harvest incidence of potato virus Y (PVY) in seed potato in Switzerland could be accurately predicted by the cumulative abundance of Brachycaudus helichrysi (from first appearance in spring up to mid-June) and that this abundance was positively correlated to the mean daily winter temperature (January-February) indicating that winter conditions could be used as an early warning signal for PVY risk in the current season. Therefore, regarding our pathosystem, forecasting A. gossypii spring flying patterns as a function of winter climatic conditions could be worth investigating in order to deploy strategic control measures before planting.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Congdon et al [22] developed an empirical model to forecast pea seed-borne mosaic virus (PSbMV) incidence in field pea crops using pre-growing season rainfall to calculate an index of aphid abundance which is used in combination with the virus infection level in the sown seed, to provide forecasts before sowing to allow sufficient time to implement control recommendations. Similarly, Steinger et al [23] observed that the post-harvest incidence of potato virus Y (PVY) in seed potato in Switzerland could be accurately predicted by the cumulative abundance of Brachycaudus helichrysi (from first appearance in spring up to mid-June) and that this abundance was positively correlated to the mean daily winter temperature (January-February) indicating that winter conditions could be used as an early warning signal for PVY risk in the current season. Therefore, regarding our pathosystem, forecasting A. gossypii spring flying patterns as a function of winter climatic conditions could be worth investigating in order to deploy strategic control measures before planting.…”
Section: Discussionmentioning
confidence: 98%
“…Forecast models are available for potatoes predicting the spread of a Potato virus Y in the current season using trap data of aphid flights ( Steinger et al., 2015 ) to optimize virus control in seed potato production. Qi et al.…”
Section: Modeling and Forecastingmentioning
confidence: 99%
“…Uit buitenlands onderzoek (Sigvald, 1992;Basky, 2002;Kirchner et al, 2011;Steinger et al, 2015) Het belangrijkste resultaat is dat duidelijk is geworden dat aardappelen de belangrijkste virusbron zijn voor de verspreiding van PVY, dit gegeven leidt tot hernieuwde aandacht voor oude adviezen en nieuwe aandachtspunten, waaronder:…”
Section: Veldonderzoek Irs Bietenvergelingsziekte In Suikerbietenunclassified